Midregion PTHrP and Human Breast Cancer Cells - Claudio Luparello (The Scientific World Journal)
PTHrP is a polyhormone undergoing proteolytic processing into smaller bioactive forms, comprising an N-terminal peptide, which is the mediator of the “classical” PTH-like effect, as well as midregion and C-terminal peptides. The midregion PTHrP domain (38-94)-amide was found to restrain growth and invasion in vitro of some breast cancer cell lines, causing striking toxicity and accelerating death; the most responsive being MDA-MB231, whose tumorigenesis was also attenuated in vivo. In addition, midregion PTHrP appears to be imported in the nucleoplasm of cultured MDA-MB231 cells and in vitro, it can bind chromatin of metaphase spread preparations and also an isolated 20-mer oligonucleotide, thereby appearing endowed with a putative transcription factor–like DNA-binding ability. The object of this review is to discuss collectively and critically both precedent and more updated data obtained in the lab, the latter arising from assays on DNA status, and gene and protein expression patterns of treated cells, aiming to check whether the cytotoxicity of the peptide may result from a reprogramming of gene expression towards apoptotic death or, instead, it is to be ascribed to an unprogrammed perturbation of cell functions.